Data-driven ethical guidelines for digitized mental health services: principal components analysis - Bapat, Chinmay; Jog, Snehal (Frontiers in Human Dynamics, 2025)
IntroductionVarious regulatory bodies have published ethical principles, codes, and/or guidelines for mental health practice globally. Although such guidelines may lend themselves equally relevant, there seems a paucity of directives specific to digital platforms such as apps utilizing AI-assisted chatbots, etc. in providing aid for mental health concerns. Exploring data-driven ethical principles for all stakeholders including the practitioners/facilitators, potential consumers, and developers of such platforms is crucial given the rapid expansion of digitized mental health support. A novel approach is proposed undertaking gap-analysis by identifying the themes of ethical concerns from practitioners’ and consumers’ perspectives.MethodThematic analysis of literature on ethics in both conventional psychotherapy and digital mental health interventions was conducted to develop a comprehensive thematic framework of ethical principles for digitized mental health care. Based on these foundational themes, a content-valid 30-item research measure was developed to administer on samples of potential consumers as well as practitioners/trainees. In order to reduce the items to meaningful components of ethical considerations, rooted in the participants’ responses, separate principal components analyses were conducted on this primary data from consumers and practitioners, respectively.ResultsPrincipal components analysis on consumers’ data revealed a single component solution, i.e., the consumers perceived a variety of ethical concerns in a unidimensional manner, suggesting that more awareness is needed for them to make better and more informed choices about their mental health care. Principal components analysis on practitioners/trainees’ data found two meaningful components. In other words, practitioners/trainees on the other hand emphasized two aspects of ethical concerns: the competency, design, accountability of a mental health app, and the rights and security that it needs to provide for its consumers.DiscussionCurrent research aimed to bridge the gap in literature with a data-driven, empirical approach to formulate ethical regulations for digitized mental health services, specifically the mental health apps. Findings from the study are proposed to benefit the developers of digital mental health apps, and organizations offering such services in ensuring ethical standards as well as effectively communicating them to the potential consumers.